1993
DOI: 10.2527/1993.7161532x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental chromium on immune responses of periparturient and early lactation dairy cows1

Abstract: The objective of the present study was to determine the effects of supplemental dietary chromium on immune responses of dairy cows subjected to physical and metabolic stresses associated with late pregnancy, calving, early lactation, and peak milk yield. Nine periparturient dairy cows were supplemented with chelated Cr (.5 ppm/d) from 6 wk prepartum (wk -6) through 16 wk postpartum (wk 16), and 10 cows were unsupplemented controls. To assess humoral immune responses, all cows were immunized with ovalbumin (OVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
2
8

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(100 citation statements)
references
References 16 publications
3
87
2
8
Order By: Relevance
“…The role of chromium in the immune responses of mammals and chicken is well established (Burton et al, 1993;Lee et al, 2003). It has also been reported that chromium modulates the immune response through its effect on cytokine release (Wang et al, 1996).…”
Section: The Effects Of Different Levels Of Nanocrpic On Immune Respomentioning
confidence: 99%
“…The role of chromium in the immune responses of mammals and chicken is well established (Burton et al, 1993;Lee et al, 2003). It has also been reported that chromium modulates the immune response through its effect on cytokine release (Wang et al, 1996).…”
Section: The Effects Of Different Levels Of Nanocrpic On Immune Respomentioning
confidence: 99%
“…Recent research has shown that supplementation with organic chromium markedly decreases serum cortisol levels ) and has beneficial effects on the immune system of stressed calves (Burton et al 1993;Mowat et al 1993). Also, chromium requirements in mammals are known to increase during stressfull conditions, particularly those associated with late pregnancy and lactation (Yang et al 1996).…”
mentioning
confidence: 99%
“…However, in the present investigation the widening of neutrophil : lymphocyte ratio in the control group vis-à -vis the narrowing of the same in the 1Cr group was not likely to be a sequel of stress, rather it might be due to an increased percentage of lymphocytes in the latter dietary group. Dietary Cr supplementation reportedly increased the proliferation of peripheral blood lymphocytes in vitro with or without mitogenic stimulation (Burton et al, 1993;Chang et al, 1994) and it is possible that supplemental Cr played the same role during the present investigation also. The goats were fed with a basal diet devoid of supplemental Cr (control) and the basal diet supplemented with 0.5 mg Cr/kg diet (1Cr) for 60 days (n 5 6 per treatment group).…”
Section: Discussionmentioning
confidence: 56%